The development of Institute of Mechanics of the Ukrainian National Academy of Sciences named after S. P. Тymoshenko (1941-1968) - M. M. Kryukov; O. V. Liashko (History of science and technology, 2018)
The chronological sequence of the main stages of the  development of  Institute of Mechanics of the Ukrainian National Academy of Sciences named after S.P. Тymoshenko and process of  its scientific directions formation during 1941-1968 are depicted in this article. The data of the structure and trends of the institute activities, theoretical and experimental researches, relations with industry and personnel training are represented. At the end of 1968 at Institute of mechanics the following departments functioned: a rheology (H.M. Savin), thermoelasticity and thermoрlasticity (A.D. Kovalenko), loudspeakers and stability of continuous environments (O. M. Huz), construction mechanics of thin-walled designs (I. Ya. Amiro), pilot studies of designs (P.S. Polyakov), plastic deformations in designs (A.I. Strelbytska), plasticity of materials (M.I. Cherniak), computing methods (Ya.M. Hryhorenko), theory of fluctuations (V.O. Kononenko), hydroelasticity (M.O. Kilchevskyi), physics and technology (S.V. Malashenko), experimental methods of a research of fluctuations (M.P. Hotyaintsev), mechanics of composite environments (H.A. Vanin), methods of calculations and designing of products from composite materials (O.A. Horoshko), modeling of designs from composite materials (V.Р. Besonov), a research of properties of new materials (I.I. Ishchenko), static durability (F.P. Beliankin), fatigue of designs (M.E. Harf), dynamics and firmness of the movement (A.N. Holubentsev). Over time reorganization and merges of some subsections was carried out. Scientific activity of institute was directed to development of fundamental research of mechanics of the solid deformed body and the general mechanics which have applied value, and participation in the solution of practical tasks. At the same time works were conducted at such main scientific directions: in the field of basic scientific research (the mechanic (statics, dynamics and stability) of elements of designs and materials at complex (power, thermal electromagnetic, etc.) influences; analytical mechanics, nonlinear fluctuations of systems of bodies and multiphase environments) in the field of applied research works (development of methods of calculations and means of a research of objects of the new equipment, development of methods of designing and creation of skilled products from high-strength composite materials, development of methods and technical means of program tests for fatigue of materials and natural elements of designs taking into account features of their operation. The powerful kernel of the Kyiv school of mechanics which concentrated and developed the activity at Institute of mechanics is created.